Toward a Culture of Consequences Performance-Based Accountability Systems for Public Services -- Executive Summary - Stecher, Brian M. (RAND Corporation, 2010)
Performance-based accountability systems (PBASs) link incentives to measured performance to improve services to the public. Research suggests that PBASs influence provider behaviors, but little is known about PBASs' effectiveness at achieving their performance goals. This document explores the design and effectiveness of nine PBASs in five sectors: child care, education, health care, public health emergency preparedness, and transportation.